Retracted: Nutrient Foramen of Fibula in Relation to Distal end, Potential Implications for Vascularised Bone Graft Surgery - N Bhatti, Amjad; Smith, C (International Journal of Human Anatomy, 2019)
Background Free vascularised fibular bone grafting has gained popularity in various Orthopaedic and Oral & maxillofacial reconstructive surgeries. The objective of the present study was to identify the morphology and topography of nutrient foramina of fibula and to determine the foraminal index (FI) of the fibula using a more surgeon friendly bony landmark. Methods The study comprised examination of 100 fibulae specimens. Each bone was divided into 03 parts and topographical analysis was performed on each section. The nutrient foramina were identified macroscopically using size 24-gauge needle. Modified Hughes formula was used to calculate the foraminal index using distance of foramen (DF) from distal end which is easier to palpate in living human beings, total length of fibula (TL); and the formula was DF/TL x100. Results With respect to fibulae, 98% had single foramen and foramen was absent in 2%. The mean foraminal index (FI) was 56% for fibulae using modified Hughes’ formula. The majority of the fibulae showed nutrient foramen in the middle 3rd in relation to distal end of fibula. Conclusion The study provides information on the morphology of nutrient foramina in relation to easily palpable landmark on living human beings, which can provide guidance to surgeon while performing microvascular bone transfer procedures.
Keywords: Anatomy; Fibula; Nutrient Foramen; Foraminal index